De familie Van Wachtendonck, de ‘Vaalser Koperwerken’ (1664-1688) en de Staten-Generaal - Weinberg, Harry (Publications de la Société Historique et Archéologique dans le Limbourg, 2023)
In the seventeenth century the city of Aachen and its surrounding region formed an important centre of brass production. In 1664, a few years after the village of Vaals, to the west of the city, had come under the sovereignty of the Dutch States General, they granted a patent giving permission for the establishment of brass production in Vaals. The Van Wachtendonck family, native of Aachen but with ties to the Unites Provinces, played a key role in this. In 1667 special measures were taken. The Van Wachtendonck family, still the only protestants to have established a brass mill in Vaals, were given tax exemptions. Furthermore, an agreement was signed on behalf of the States General with the abbot of Kornelimünster, in whose territory calamine, an essential material to produce brass, was found. The States General introduced a special import duty on brass products not made with calamine from this territory. This import duty remained in place until 1688, despite repeated protests from other brass producers. It appears that the Van Wachtendonck family may also have used their position as representatives of the States General in Aachen for additional personal gain. The attempt of the States General to draw brass production to Vaals was, however, never very successful and activities in Vaals ended after only a few decades.